Sampah Plastik sebagai Konsekuensi Modernitas dan Upaya Penanggulangannya - Alfitri Alfitri; Helmi Helmi; Slamet Raharjo; Afrizal Afrizal (Jurnal Sosiologi Andalas, 2020)
Plastic waste has become one of the most worrying global environmental problem. Increased population, urbanization, and consumptive lifestyles have increase the use of plastic. Poorly waste management system and unsupportive behavior are the factors of plastic waste problem. According to Giddens, it can be seen that the plastic problem is a consequence of modernity. Capitalism which emphasizes packaging is one of the consequences of modernity. Innovative and efficient production processes are believed can develop new economies that use a lot of recycled materials. With Giddens framework as well, the behavior of plastic producers and consumers should be able to move from unconscious motivation to practical consciousness, and discursive consciousness. Through this can be expected to form behavior of the use of plastics that are more environmentally friendly.